PHARMACEUTICAL CONTAMINATION, WATER QUALITY ASSESSMENT AND ECOTOXICOLOGICAL EVALUATION OF THE SURFACE WATERS OF THE SANGÃO RIVER, SANTA CATARINA, BRAZIL - Michele D. Freitas; Samira Leila Baldin; Eduardo P. Rico; James W. Barlow; Laíse D. S. Rosa; Silvia Dalbó; Tânia Mara Pizzolato; Patrícia A. Amaral (Química Nova)
The waters of the carboniferous basin located in the South of the Brazilian State of Santa Catarina, which are comprised of the hydrographic basins of the Urussanga, Tubarão and Araranguá Rivers (HBA), are an important hydrological resource. Due to the importance of the Sangão River, we evaluated the quality of its surface waters through detection of pharmaceutical contaminants and evaluation of physicochemical parameters. Six contaminants were detected in analyzed samples, including caffeine in all samples. Notable parameters included pH (observed range between 3-7.5), dissolved oxygen (1.08-9.52 mg mL-1), total iron (2.05-56.7 mg L-1), conductivity (2.10-1755 µS cm-1), biochemical oxygen demand (2.5-7.5 mg mL-1), phosphorus (0.02-0.29 mg L-1) and thermotolerant coliforms (values > 9.4 × 103 colony-forming unit (CFU) per 100 mL). We determined the water quality index (WQI) of the samples and performed an acute ecotoxicological study using zebrafish embryos. The results of the WQI revealed that although the source (N1) was classified as regular, samples collected upstream (RS2) and downstream (RS3) of the wastewater treatment plant (WWTP) were considered bad. In the ecotoxicological analysis, all embryos tested in groups RS2 and RS3 were not viable 24 h post-fertilization, although those collected at source survived the experiment. Collectively, our results inform the conclusion that the surface water quality of the Sangão River is impacted from its source onwards, and that remedial strategies are warranted.